The Effect Of Principal Leadership And Teacher’s Professionalism On Teachers Working Performance At Beacon Academy Kelapa Gading North Jakarta - Ibnu Susilo; Supandi Supandi; Muhammad Anhar (Indonesian Journal of Business, Accounting and Management (IJBAM), 2020)
Abstract—This study aims to analyze the effect of principal leadership on teacher performance at Beacon Academy Kelapa Gading, North Jakarta. Analyzing the effect of teacher professionalism on teacher performance at Beacon Academy Kelapa Gading, North Jakarta. As well as analyzing the influence of school principal leadership and professionalism on the performance of teachers at Beacon Academy Kelapa Gading, North Jakarta. This research method is a quantitative method. The object of this research is the Beacon Academy Kelapa Gading School, North Jakarta. The type of sampling chosen in this study is the Non Probability Sampling technique, namely Saturated Sampling (census). While the subjects or respondents (informants) selected in this study were Beacon Academy school teachers who had a direct connection to the topic, because this research was a case study, so the parties involved were used as respondents. While the source of data in this study is primary data processed using SPSS 25. The test used in this study is the classical assumption test (Normality, Heteroscedasticity, Multicollinearity and Autocorrelation), hypothesis testing (multiple regression test, coefficient of determination R2, partial test and simultaneous test). The results of this study indicate that: (1) Principal leadership partially affects teacher performance, (2) teacher professionalism does not partially affect teacher performance, and (3) principal leadership and teacher professionalism affect teacher performance simultaneously.